Military history's most wanted the top 10 book of improbable victories, unlikely heroes, and other martial oddities - Brooks, M. Evan (Brassey's most wanted series, 2002)
This volume chronicles 700 of the most outlandish commanders, battles, and accomplishments in military history, from ancient to present times and from all around the globe. Its 70 lists include warfare's top ten winners, losers, traitors, entertainers, war novels and movies.